Academic sociology: the alarming rise in predatory publishing and its consequences for Islamic economics and finance - Zubair Hasan (ISRA International Journal of Islamic Finance, 2018)
Purpose: The purpose of this paper is to explore the causes and impact of predatory online publishing on Islamic economics and finance. Design/methodology/approach The method adopted involves a library literature scan to identify the origin and expansion of predatory publishing, as references listed in the paper show. The personal experience and observation of the author over the decades of teaching at various universities endorses the evidence. Findings The focus on 'publish or perish' has led to division of Islamic scholars into conservative and modern economists, and it led to the overuse of mathematical and parametric modeling to the disadvantage of the discipline essentially imbued with unquantifiable ethical norms and values. Practical implications The study seeks to induce fruitful and purposive change in the research designs and direction of Islamic economics and finance. Originality/value This research initiates discussion on predatory publishing, an issue so far untouched in Islamic economics. It explores its impact on the discipline and suggests ways to curb the malady.
Keywords: 330; Econometric modeling; Islamic economics; Predatory publishing